PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN KONSUMEN PADA PT. SYAKIRASYA WISATA MANDIRI - Hikam, Manarul; Mukhsin, Moh. (NATUJA: Jurnal Ekonomi Syariah, 2024)
In the era of globalization, it is important not to ignore the role of humans in the world of work. Very tight competition in the same field of work makes people involved in it want to make optimal contributions to society, especially in the service sector in certain industries or fields of work. This research aims to analyze the influence of service quality and price simultaneously and partially on consumer satisfaction at PT. Syakirasya Wisata Mandiri. This research uses quantitative methods with data processing using multiple linear regression analysis methods. The sampling technique uses non-probability sampling with a purposive sampling selection method. The research results show that service quality and price simultaneously have a significant effect on customer satisfaction at PT. Syakirasya Wisata Mandiri. The research results show partially that the service quality variable influences consumer satisfaction at PT. Syakirasya Wisata Mandiri, it is known that the calculated T value (3.796) is more than T table (2.014) with a significant value of 0.000. Meanwhile, the price variable partially has no effect on consumer satisfaction at PT. Syakirasya Wisata Mandiri, it is known that the calculated T value (1.813) < T table (2.014) with a significant value of 0.044. The results of the coefficient of determination test show that customer satisfaction can be explained by service quality and price by 57.5%, while (100%-57.5%= 42.5%) is influenced by other variables not included in the research.